Post-Conflict Recovery: Business Opportunities and Economic Reconstruction in Papua - Novyta Sari (Mustard Journal De Ecobusin, 2024)
This study investigates post-conflict recovery, business opportunities, and economic reconstruction in Papua, Indonesia. A purposive sampling technique was employed to select participants with direct experience in post-conflict recovery efforts. Data were collected using structured questionnaires and analyzed using statistical methods including paired-samples t-tests, regression analyses, ANCOVA, and Pearson correlational analyses. The results reveal positive perceptions of economic reconstruction compared to business opportunities among participants. Significant improvements in perceptions of business opportunities were observed following targeted interventions. Factors influencing business opportunities include economic reconstruction, infrastructure development, government support, and community engagement. Age group did not significantly impact perceptions of business opportunities. A positive correlation was found between perceptions of business opportunities and economic reconstruction, highlighting their interdependence. This study provides insights into the complexities of post-conflict recovery and underscores the importance of holistic approaches for sustainable development.